2020
DOI: 10.1016/j.bbamcr.2020.118825
|View full text |Cite
|
Sign up to set email alerts
|

A cell cycle checkpoint for the endoplasmic reticulum

Abstract: The generation of new cells is one of the most fundamental aspects of cell biology. Proper regulation of the cell cycle is critical for human health, as underscored by many diseases associated with errors in cell cycle regulation, including both cancer and hereditary diseases. A large body of work has identified regulatory mechanisms and checkpoints that ensure accurate and timely replication and segregation of chromosomal DNA. However, few studies have evaluated the extent to which similar checkpoints exist f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…Accordingly, eukaryotic cell cycle regulation integrates a huge multitude of internal and external signals to optimize survival. Failures in these processes reduce cell survival and, in higher metazoans, lead to cancer, and other diseases ( Moriel-Carretero et al, 2019 ; She et al, 2019 ; Klemm et al, 2020 ; Lai et al, 2020 ; Matellán and Monje-Casas, 2020 ; Niwa, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, eukaryotic cell cycle regulation integrates a huge multitude of internal and external signals to optimize survival. Failures in these processes reduce cell survival and, in higher metazoans, lead to cancer, and other diseases ( Moriel-Carretero et al, 2019 ; She et al, 2019 ; Klemm et al, 2020 ; Lai et al, 2020 ; Matellán and Monje-Casas, 2020 ; Niwa, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that Tm-induced ER stress is known to cause cytokinesis arrest in yeast [27,28]. As sse1Δ strain continued to grow in the presence of Tmstress, it prompted us to check the cell division status of this strain following ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…As sse1Δ strain showed prominent growth fitness during long-standing Tmstress and tunicamycin stress is known to cause cell division arrest in yeast [27,28], it was interesting to check the status of cell division of this deletion strain during Tm-induced ER stress. Furthermore, we found that mitotic cell cycle and cell cycle pathways to be significantly upregulated in Tm-treated sse1Δ cells by pathway enrichment analysis of the transcriptome data, as described before (Figure 5C).…”
Section: Sse1 Plays a Crucial Role In Controlling Er-stress-induced C...mentioning
confidence: 99%
“…While one study suggests this may be due to excessive integrin-based extracellular matrix adhesive tension that ultimately interferes with contractility of the actin-myosin cytokinetic ring (53), there are many routes to cytokinesis failure caused by reduced or elevated Rho-signaling (54). Endoplasmic reticulum (ER)-stress itself can lead to cytokinesis failure (55, 56). Moreover, PKR, a dsRNA-dependent Protein Kinase and upstream activator of the ISR, can be activated by mitosis onset, where nuclear membrane breakdown releases endogenous dsRNAs that bind and activate PKR (57).…”
Section: Discussionmentioning
confidence: 99%